2020
DOI: 10.1371/journal.pone.0230019
|View full text |Cite
|
Sign up to set email alerts
|

Angular momentum regulation may dictate the slip severity in young adults

Abstract: Falls cause negative impacts on society and the economy. Slipping is a common initiating event for falling. Yet, individuals differ in their ability to recover from slips. Persons experiencing mild slips can accommodate the perturbation without falling, whereas severe slipping is associated with inadequate or slow pre-or post-slip control that make these individuals more prone to fall. Knowing the discrepancies between mild and severe slippers in kinematic and kinetic variables improves understanding of advers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…This meant that the PD group experienced a greater lateral shift onto their leading limb that would lead their center of pressure to travel closer to the lateral edge of their base of support (Chiovetto et al, 2018;Herr and Popovic, 2008). Poor regulation of frontal angular momentum has been shown to have implications regarding severity of a slip should one occur (Nazifi et al, 2020). During weight transfer, the hip extensors and ankle dorsiflexors are most active in the sagittal plane (Neptune and McGowan, 2011), and in the frontal plane, the leg abductors are most active (Neptune and McGowan, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This meant that the PD group experienced a greater lateral shift onto their leading limb that would lead their center of pressure to travel closer to the lateral edge of their base of support (Chiovetto et al, 2018;Herr and Popovic, 2008). Poor regulation of frontal angular momentum has been shown to have implications regarding severity of a slip should one occur (Nazifi et al, 2020). During weight transfer, the hip extensors and ankle dorsiflexors are most active in the sagittal plane (Neptune and McGowan, 2011), and in the frontal plane, the leg abductors are most active (Neptune and McGowan, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This study was further limited by the choice to normalize WBAM using walking velocity. Though this is the technique most used in the literature (Herr and Popovic, 2008;Silverman et al, 2012;Martelli et al, 2013;Nolasco et al, 2019;Nazifi et al, 2020), it should be noted that due to the cross product in Eq.1, sagittal walking velocity does not contribute to the frontal plane angular momentum. Normalizing frontal plane angular momentum by disparate walking velocities can artificially skew the magnitude of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we presented our second hypothesis and demonstrated that the peak sagittal and frontal plane angular momentum of the trunk and non-dominant arm during the slipping timeline, respectively, were significant in classifying falls and recoveries. Despite extensive literature on the significance of peak trunk extension angle to both falls and recoveries (9,13,17,19,23,29,(42)(43)(44)(45), our variable selection process generated a model based on arm adduction angular momentum. This would indicate that bracing for impact by increasing arm adduction angular momentum is associated with higher fall probability.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore unsurprising to find a movement synergy identified during the double-support phase of normal-walking was most relevant to DP as this gait-phase plays a proactive role in dynamic balance control. Interestingly [ 51 ], was unable to find differences between mild- and severe-slippers in terms of baseline sagittal plane angular momentum, centre-of-mass height, single/double-support duration or upper-body extremity kinematics but did find differences between groups during perturbed-walking. The results of the current study suggest PCA derived movement synergies may be useful in identifying such differences relevant to slip severity during normal-walking trials.…”
Section: 1 Discussionmentioning
confidence: 99%